Hyperphosphorylation of mutant influenza virus matrix protein, M1, causes its retention in the nucleus. - Whittaker, G (1995)
The matrix (M1) protein of influenza virus is a major structural component, involved in regulation of viral ribonucleoprotein transport into and out of the nucleus. Early in infection, M1 is distributed in the nucleus, whereas later, it is localized predominantly in the cytoplasm. Using immunofluorescence microscopy and the influenza virus mutant ts51, we found that at the nonpermissive temperature M1 was retained in the nucleus, even at late times after infection. In contrast, the viral nucleoprotein (NP), after a temporary retention in the nucleus, was distributed in the cytoplasm. Therefore, mutant M1 supported the release of the viral ribonucleoproteins from the nucleus, but not the formation of infectious virions. The point mutation in the ts51 M1 gene was predicted to encode an additional phosphorylation site. We observed a substantial increase in the incorporation of 32Pi into M1 at the nonpermissive temperature. The critical role of this phosphorylation site was demonstrated by using H89, a protein kinase inhibitor; it inhibited the expression of the mutant phenotype, as judged by M1 distribution in the cell. Immunofluorescence analysis of ts51-infected cells after treatment with H89 showed a wild-type phenotype. In summary, the data indicated that the ts51 M1 protein was hyperphosphorylated at the nonpermissive temperature and that this phosphorylation was responsible for its aberrant nuclear retention.